QDGRP : A hybrid QoS Distributed Genetic routing protocol for Wireless Sensor Networks - Koulali, M.; Kobbane, A.; El Koutbi, M.; Azizi, M. (2012 International Conference on Multimedia Computing and Systems, 2012)
Nature-inspired routing protocols have been subject to a great research activity. Their decentralized nature and low requirements make them highly suitable for Wireless Sensor Networks (WSN) where individual nodes operate without central control and without global overview of the network status to achieve global tasks. This paper proposes a hybrid QoS routing protocol for WSN based on a customized Distributed Genetic Algorithm (DGA) that accounts for delay and energy constraints. The proposed protocol (QDGRP) is compared to AODV w.r.t several performance metrics : end-to-end delay, throughput, packet delivery ratio and energy efficiency. The realized simulations show that QDGRP outperforms AODV and manages to achieve very good performances for various deployment scenarios.